Difference between revisions of "Math 22 Lagrange Multipliers"
Jump to navigation
Jump to search
Line 15: | Line 15: | ||
!Solution: | !Solution: | ||
|- | |- | ||
− | |<math>\ | + | |So, <math>F(x,y,\lambda)=f(x,y)-\lambda g(x,y)=xy-\lambda (x+y-14)=xy-\lambda x -\lambda y+14\lambda</math> |
|- | |- | ||
− | |<math>\ | + | |<math>F_x(x,y,\lambda)=y-\lambda</math> |
+ | |- | ||
+ | |<math>F_y(x,y,\lambda)=x-\lambda</math> | ||
+ | |- | ||
+ | |<math>F_{\lambda}(x,y,\lambda)=-x-y+14</math> | ||
|} | |} | ||
Revision as of 08:54, 18 August 2020
Method of Lagrange Multipliers
If has a maximum or minimum subject to the constraint , then it will occur at one of the critical numbers of the function defined by . In this section, we need to set up the system of equations:
Example: Set up the Lagrange Multipliers:
1) Maximum: and Constraint
Solution: |
---|
So, |
2) Maximum: and Constraint
Solution: |
---|
This page were made by Tri Phan